2019
DOI: 10.1038/s41386-019-0553-y
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin involvement in trauma processing—exploring candidate neurocognitive mechanisms of preventing post-traumatic stress symptoms

Abstract: The angiotensin-II antagonist losartan is a promising candidate that has enhanced extinction in a post-traumatic stress disorder (PTSD) animal model and was related to reducing PTSD symptom development in humans. Here, we investigate the neurocognitive mechanisms underlying these results, testing the effect of losartan on data-driven and contextual processing of traumatic material, mechanisms proposed to be relevant for PTSD development. In a double-blind between-subject design, 40 healthy participants were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Recently reported data from a separate large cross‐sectional study of trauma‐exposed civilians have demonstrated the presence of enduring alterations of the renin‐angiotensin‐aldosterone system (RAAS) in adults exposed to trauma during childhood and/or adulthood providing an empirical foundation for the association of ACE inhibitor and ARB prescription with reduced PTSD symptom severity. Further, translational research investigating the impact of acute administration of the ARB, losartan, on the acquisition and extinction of fear in healthy human participants has provided support for a possible role of ARBs in the prevention and treatment of PTSD by way of effects on the RAAS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently reported data from a separate large cross‐sectional study of trauma‐exposed civilians have demonstrated the presence of enduring alterations of the renin‐angiotensin‐aldosterone system (RAAS) in adults exposed to trauma during childhood and/or adulthood providing an empirical foundation for the association of ACE inhibitor and ARB prescription with reduced PTSD symptom severity. Further, translational research investigating the impact of acute administration of the ARB, losartan, on the acquisition and extinction of fear in healthy human participants has provided support for a possible role of ARBs in the prevention and treatment of PTSD by way of effects on the RAAS.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence derived from real-time neurofeedback training further pronounce that PTSD patients showed a clinical reliance of top-down emotional regulation deficits in PFC-amygdala connections ( Nicholson et al, 2017 ). EMN was of crucial for contextual processing of stimuli information in PTSD patients ( Shkreli et al, 2020 ). Generalizing threatening experiences to daily life in PTSD patients was related to the differential neural coding of safety and threat signals in the hippocampus and mPFC ( Shalev et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence from animal models and human findings have suggested a crucial role of the renin-angiotensin system (RAS) in emotion and memory formation which may overlap with processes relevant for the development of PTSD (1517). Different lines of research have indicated an important role of the RAS in the development of PTSD such that (1) blood levels of renin were elevated in individuals with trauma-experience (18), (2) treatment with angiotensin blockers, particularly the angiotensin II type 1 receptor antagonist losartan (LT) during trauma exposure reduced the incidence of PTSD (19, 20), and (3) administration of LT in healthy controls also reduced autonomic stress reactivity during experimental trauma induction (21) and shifted emotional reactivity from negative to positive information (22, 23). While these findings support that targeting the RAS via LT may prevent the development of PTSD by modulating emotional or memory formation processes, the underlying behavioral and neurobiological mechanisms have not been examined.…”
Section: Introductionmentioning
confidence: 99%